Pension reform and labor market incentives - Walter H. Fisher; Christian Keuschnigg (Institute for Advanced Studies (IHS), 2007)
This paper investigates how parametric reform in a pay-as-you-go pension system with a tax benefit link affects retirement incentives and work incentives of prime-age workers. We find that postponed retirement tends to harm incentives of prime-age workers in the presence of a tax benefit link, thereby creating a policy trade-off in stimulating aggregate labor supply. We show how several popular reform scenarios are geared either towards young or old workers, or, indeed, both groups under appropriate conditions. We also provide a sharp characterization of the excess burden of pension insurance and show how it depends on the behavioral supply elasticities on the extensive and intensive margins and the effective tax rates implicit in contribution rates.
Keywords: H55; J26; 330; pension reform; retirement; hours worked; tax benefit link; actuarial adjustment; excess burden; Rentenreform; Altersgrenze; Arbeitsangebot; Ökonomischer Anreiz; Steuer; Gesetzliche Rentenversicherung; Excess Burden; Theorie